En tilfældig slægt - Toftdahl, Hellmut (Grundtvig-Studier, 1991)
‘Just a Family’ Birgit Michelsen: ‘The Catechist, the Dean, and the Socialist’. The History of Three Generations. Published by Anis, Århus, 1989. By Hellmut Toftdahl The writer has written about three people in the history of her family, for whom Christianity was a deeply personal matter. Their crises reflect the crisis which the Christian Church underwent in those years. We also meet several other people in the book, sons and daughters of the three. Their scruples and rebellions, ranging from radical free-thinking to an involvement in German Socialism, are woven together into a vivid presentation of the history of ideas of the time. The main character of the book is the restless, fascinating Christian, who ended his life in Leipzig as a Socialist and naturalized German. With his doubt about the ‘truths’ he had inherited from his family of clergymen, and in his search for the ‘right thinking’, he was ahead of his time. In his honesty and need to be true to himself, he had a good deal in common with both Søren Kierkegaard and Grundtvig, whose contemporary he was. In a Grundtvig context the book is interesting because it affords personal evidence of the ecclesiastical and existential forces that Søren Kierkegaard and Grundtvig, with their liberating theology, were up against among the representatives of the established understanding of Christianity of the time.